Endangered languages of Austronesia - Florey, Margaret J. (Oxford : Oxford University Press, 2010)
This text explores the challenges to linguistic vitality confronting many minority languages in the highly diverse and geographically far-flung Austronesian language family. The contributions bring together Indigenous language activists and academic researchers with a long-standing commitment to language documentation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Austronesian languages; Endangered languages -- Pacific Area